Mrs. Patty is batty! - Gutman, Dan.; Paillot, Jim (New York : HarperTrophy, 2006)
A.J. and the other students at Ella Mentry School brave trick-or-treating at the school secretary's house, even though it is supposedly haunted.
630
Accelerated Reader AR
Keywords: Halloween -- Juvenile fiction; Schools -- Juvenile fiction; Humorous fiction